Effects of Copper Feeding Strategy on Growth Performance of Nursery Pigs - Samantha A. Swanson; Jordan T. Gebhardt; Jason C. Woodworth; Mike D. Tokach; Joel M. DeRouchey; Robert D. Goodband; Katelyn N. Gaffield; Matt Einarson (Kansas Agricultural Experiment Station Research Reports, 2025)
A total of 2,204 pigs (PIC 337 × 1050, initially 11.76 ± 0.19 lb) were used in a 38-d study to determine the effect of copper (Cu) feeding strategy on the growth performance of nursery pigs. Pigs were weaned at approximately 20 d of age and randomly allotted to pens with 29 pigs per pen. Pens of pigs were blocked by initial BW and allotted to one of four treatments in a randomized complete block design with 19 pens per treatment across two rooms. Treatment diets were formulated in three phases and fed based on feed budgets of 4 lb/pig and 12 lb/pig for phases 1 and 2, respectively, and phase 3 was fed for the remainder of the trial. Four Cu feeding strategies consisting of increased levels of Cu in the different nursery phases were evaluated. Feeding strategy 1 served as the control with no pharmacological levels of Cu, strategy 2 included pharmacological Cu levels in only phase 3, strategy 3 consisted of pharmacological Cu in phases 2 and 3, and strategy 4 included pharmacological Cu in all three phases. Within each experimental phase, there were two diets provided, either a base level of Cu (17 mg/kg) or pharmacological levels (167 mg/kg) of Cu. The base level of Cu was provided from CuSO in the vitamin/trace mineral premix. In diets that fed Cu above the base level, 150 mg/kg Cu from tribasic copper chloride (SAM Nutrition, Bloomington, MN) was added in addition to the base level. Diets followed common industry practice of Zn supplementation using ZnO in phases 1 and 2 to provide Zn inclusion above basal nutritional levels (approximately 3,000 mg/kg Zn in phase 1, approximately 2,000 mg/kg Zn in phase 2, and 110 mg/kg Zn in phase 3 for all treatments). Pigs were weighed and feed disappearance was measured to determine ADG, ADFI, and feed efficiency. From d 0 to 10 (phase 1), there was no evidence of difference (P > 0.10) in performance between pigs fed the base level of Cu and pigs fed a diet containing 167 mg/kg added Cu. From d 10 to 24 (phase 2), pigs fed added Cu had a greater ADG (P = 0.012) and ADFI (P = 0.021) compared to pigs fed the base level of Cu, with no evidence of a difference for F/G. Pigs fed added Cu for phases 1 and 2 had a greater ADG than pigs fed the control with no pharmacological levels of Cu (P = 0.047), with pigs fed pharmacological Cu levels in only phase 3, and pigs fed pharmacological Cu in phases 2 and 3 being intermediate. From d 24 to 38 (phase 3), there were no differences in performance between pigs fed the base level Cu and those fed diets with added Cu. However, pigs fed pharmacological Cu in phases 2 and 3 had numerically greater ADG compared with the other feeding strategies. There were no differences between feeding strategies in overall growth performance (d 0 to 38) or removals and mortality. These data suggest that when pharmacological levels of Zn are used, nursery growth performance can be improved by the addition of pharmacological levels of Cu in the phase 2 diet; however, the improvement did not have an effect on the overall ADG, ADFI, feed efficiency, removals or mortality.
Keywords: nursery pigs; tribasic copper chloride